Complete Genome Sequencing of Lactobacillus plantarum UNQLp 11 Isolated from a Patagonian Pinot Noir Wine - Iglesias, N.G.; Brizuela, N.S.; Tymczyszyn, E.E.; Hollmann, A.; Valdés La Hens, D.; Semorile, L.; Bravo-Ferrada, B.M. (South African Journal of Enology and Viticulture, 2020)
Lactobacillus plantarum UNQLp 11 strain was isolated from a Patagonian Pinot noir wine at the oldest commercial winery (110 years old) in General Roca, North Patagonia, Argentina, and has demonstrated its ability to survive during winemaking processes and successfully carry out malolactic fermentation. This work aimed to obtain the whole assembled genome of the UNQLp 11 strain, analysing its architecture and the possible functions of the predicted genes from the oenological properties of this strain. The genome size is 3 534 932 bp, with a mean GC content of 44.2%, 3 412 CDS, 80 transposons and 148 tandem repeats. A comparison between the genome size and gene content of 14 Lb. plantarum strains from different origins was performed, and UNQLp 11 exhibited the largest size. The in silico genome-wide analysis allowed us to confirm the existence of genes encoding enzymes involved in the synthesis of several metabolites of oenological interest, in addition to bacteriocins and exopolysaccharides. Furthermore, it is possible to speculate on this strain’s adaptation to different environments, as it is able to use diverse substrates for its growth. All these features suggest the potential of UNQLp 11 to be a good starter culture for malolactic fermentation.